Hyaluronidase Impairs Neutrophil Function and Promotes Group B Streptococcus Invasion and Preterm Labor in Nonhuman Primates - Michelle Coleman (American Society for Microbiology, 2021)

(untitled)
Group B streptococci (GBS) are bacteria that commonly reside in the female lower genital tract as asymptomatic members of the microbiota. However, during pregnancy, GBS can infect tissues at the maternal-fetal interface, leading to preterm birth, stillbirth, or fetal injury.